Disseminated fusariosis emerged from prolonged local genital infection after cord blood transplantation. Issue 8 (August 2018) - Okada, Kohei; Endo, Tomoyuki; Hashimoto, Daigo; Saga, Tomoyuki; Ara, Takahide; Ogasawara, Reiki; Yasumoto, Atsushi; Ibata, Makoto; Takahata, Mutsumi; Shigematsu, Akio; Kondo, Takeshi; Muraosa, Yasunori; et al.
Abstract: Disseminated fusariosis (DF) is a rare life threatening fungal infection in immunocompromised hosts. We herein report a case of a fatal DF mimicking varicella zoster virus (VZV) infection that was emerged from a localized genital infection during cord blood transplantation (CBT) in a patient with severe aplastic anemia (SAA). The patient developed an ulcer following small painful vesicles mimics herpes simplex virus infection (HSV) on the glans penis before CBT, but a Fusarium species was identified. Despite administration of voriconazole, liposomal amphotericin B and granulocyte transfusion, the lesion was extended to extensive skin looked like VZV infection and the patients died after CBT. Massive fusarium infiltration was detected in multiple organs at autopsy. A genetic analysis of the mold identified Fusarium solani after his death. It should be noted that in patients with fusarium infection, localized and disseminated lesions of fusarium infection sometimes mimic HSV and VZV infections, which hampers an early diagnosis.